The effect of two training methods on the dental students\' ability in shade matching - Mehdi Abbasi; Aghil Rahmani; Ladan Ranjbar Omrani; Zohreh Moradi; Masumeh Hasani Tabatabaei; Sara Valizadeh (Tehran University of Medical Sciences, 2018)
Background and Aims: Color is the most important and complicated part of aesthetic dentistry. The tooth color matching of restorations is considered as one of the most difficult tasks in the restorative dentistry. The aim of this study to evaluate the effect of two training methods on the dental students' ability in determining tooth color matching. Materials and Methods: In this study, 40 dentistry students participated which randomly allocated into two groups. The first group consisted of students who learned teeth color matching methods practically. In the second group, training booklet was used for learning. Using Vita Classic shade guide series, 4 color samples were chosen and the students of each group were asked to determine samples' color, before, after and one month after the training. Results: Booklet learning group was more successful in determining fourth color sample. However, in no studied group and no used samples, the results of one month after learning were not better than that of before learning. Also generally, no significant relationship was found between the color matching accuracy, using glasses, and sex of participants. Conclusion: The use of booklet learning was more effective than practical learning in color matching accuracy for dental students. Also, using glasses and sex were not effective on their color matching accuracy.